2019
DOI: 10.1002/psp.2252
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and neighbourhood attainment in England and Wales: A study of second generations' spatial integration

Abstract: Ethnic minorities' spatial concentration and their predominance in deprived areas are two well‐known patterns that characterise Britain's social landscape. However, little is known about ethnic minorities' opportunities for spatial integration, especially those of the second generations. Using a large‐scale longitudinal data set of England and Wales covering a 40‐year period (1971–2011), in combination with aggregated census data, the article examines ethnic inequalities in access to neighbourhoods with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…However, we might also think of an alternative explanation, associated to neighbourhood dynamics. In line with spatial assimilation theories, for which there is some evidence in Europe (Schaake, Burgers, and Mulder 2013;Zuccotti 2019), immigrants' neighbourhood segregation should diminish in areas with higher socioeconomic resources, since better-off immigrants often move to wealthier and whiter areaswhile poorer immigrants remain constrained to ethnic enclaves. If this is the case, one explanation for the absence of an effect might be precisely the higher degree of residential and/or labour market segregation of immigrants in poorer NUTS3 areas, which would reduce both contact with natives and the threat of job competition (or competition for economic resources).…”
Section: Discussionmentioning
confidence: 76%
“…However, we might also think of an alternative explanation, associated to neighbourhood dynamics. In line with spatial assimilation theories, for which there is some evidence in Europe (Schaake, Burgers, and Mulder 2013;Zuccotti 2019), immigrants' neighbourhood segregation should diminish in areas with higher socioeconomic resources, since better-off immigrants often move to wealthier and whiter areaswhile poorer immigrants remain constrained to ethnic enclaves. If this is the case, one explanation for the absence of an effect might be precisely the higher degree of residential and/or labour market segregation of immigrants in poorer NUTS3 areas, which would reduce both contact with natives and the threat of job competition (or competition for economic resources).…”
Section: Discussionmentioning
confidence: 76%
“…1 Intergenerational persistence in the ethnic composition of neighborhoods is also stronger than the corresponding patterns for neighborhood-level unemployment rates. For the UK, Zuccotti (2019) found that that second-generation immigrants-especially those of Pakistani, Bangladeshi, and African background-are more likely than natives to live in immigrantdense and socioeconomically disadvantaged neighborhoods even after accounting for individual socioeconomic resources, family background, and childhood neighborhood characteristics. Interestingly, persistence in ethnic neighborhood composition is stronger among second-generation immigrants than for natives, while such a pattern is less consistent for neighborhood socioeconomic deprivation.…”
Section: Previous Literaturementioning
confidence: 99%
“…However, recent research from the United States have found that second-generation immigrants experience considerable upward contextual mobility out of deprived childhood neighborhoods (Tran 2020). In contrast, European studies report strong intergenerational reproduction in deprived neighborhood contexts among immigrant populations in France (McAvay 2018), the Netherlands (de Vuijst, van Ham and Kleinhans 2017), the United Kingdom (Zuccotti 2019) and Scandinavia (Gustafsson, Katz and Österberg 2017;Nordvik and Hedman 2019;Van Ham et al 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although there is no doubt that minority neighbourhood attainment outcomes are lower, and more persistent (Zuccotti, 2019), than neighbourhood outcomes in general, there is much greater dynamism and a more complex pattern of residential outcomes as Brazil and Clark (2017) show, and average outcomes alone do not capture this complexity. Because of this tension between studies using average outcomes and at least one study that analyses the distributional outcomes, it is important to explore further the question of just how resilient neighbourhood constraints are for context mobility.…”
Section: Introduction and Framingmentioning
confidence: 99%